TRIGLYCERIDE-GLUCOSE INDEX AND CARDIOVASCULAR EVENTS IN NON-DIABETIC HYPERTENSION: SECONDARY ANALYSIS OF SPRINT - Richard Kazibwe, MD, MS (Elsevier, 2024)
Therapeutic Area: ASCVD/CVD Risk Factors Background: The triglyceride-glucose (TyG)-index is an inexpensive novel surrogate marker of insulin resistance (IR) that has been associated with cardiovascular disease (CVD). Despite known associations, the role of the TyG-index in predicting cardiovascular events in individuals with hypertension but without diabetes remains insufficiently explored. In this analysis, we examined the relationship of TyG-index and the risk of cardiovascular events among participants in the Systolic Blood Pressure Treatment Intervention Trial (SPRINT). The SPRINT trial investigated the benefit of a systolic blood pressure (SBP) goal of <120 mm Hg compared with <140 mm Hg. Methods: The study included a total of 9,323 participants, characterized by high-risk hypertension without diabetes from the SPRINT trial, conducted between 2010 and 2016. Baseline insulin resistance was determined using TyG index computed as In[fasting triglyceride level (mg/dl) × fasting plasma glucose (mg/dl)/2]. The participants were categorized based on their TyG index (Table). We used multivariable-adjusted Cox regression to examine the association of TyG index and the primary outcome in SPRINT, defined as a composite of myocardial infarction, other acute coronary syndromes, stroke, acute heart failure, or cardiovascular (CV) death. Results: After a median follow-up of 3.8 years, 725 primary outcome events were observed. The primary outcome incidence rate (per 1,000 person-years) among participants in tertile 1, tertile 2 and tertile 3 was 18.0, 22.5 and 23.5, respectively. In the multivariate Cox model, each one (1) unit increase in TyG index was associated with a significantly higher risk of the primary outcome (hazard ratio [HR], 1.28; 95% confidence interval [CI], 1.10 to 1.50; p-value=0.001). Participants in the highest TyG index tertile had a 33% higher risk of cardiovascular events compared to those in the lowest tertile (Figure). Conclusions: These findings suggest the TyG-index could serve as a cost-effective tool for identifying high-risk individuals among patients with hypertension who do not have diabetes mellitus, potentially guiding more personalized treatment strategies.